Green Organizational Culture and Organizational Performance: The Mediating Role of Green Innovation and Environmental Performance - Imran, M.; Arshad, I.; Ismail, F. (Jurnal Pendidikan IPA Indonesia, 2021)
This study aims to develop and test a theoretical model that empirically examines how green organizational culture affects organizational performance. Additionally, investigated and statistically explored the study model's and their mediating role of environmental performance and green innovation, which had previously received little attention. For the sample size of 170 respondents, a quantitative approach was used. In addition, convenient random sampling was utilized to get data from the respondents. Data was gathered from a field survey utilizing a closed-ended questionnaire from Malaysia's industrial and service organizations from Malacca, Johor, Selangor, and Kedah states. The structural equation modelling approach was used to achieve the research purpose. Green organizational culture was a significant predictor of green performance in this research. Furthermore, the findings reveal that environmental performance and green innovation fully mediate the relationship between green organizational culture and organizational performance. However, this study has several limitations that lead to future research directions. The study's most significant drawback is that the data is collected merely from Malaysian industries, making generalization difficult. In addition, the cross-sectional data adds further restrictions to it. Nevertheless, by addressing organizational performance, which has not been empirically examined, this research adds to the current literature on green organizational culture, environmental performance, and green innovation. Furthermore, this research also presents a novel theoretical explanation for the relationships by understanding the mediating role of environmental performance and green innovation.